2009
DOI: 10.1308/003588409x359349
|View full text |Cite
|
Sign up to set email alerts
|

The Timing of Calcium Measurements in Helping to Predict Temporary and Permanent Hypocalcaemia in Patients Having Completion and Total Thyroidectomies

Abstract: Serum calcium levels measured 6 hours' post-surgery and on day 1 postoperatively can be useful in predicting if the patient will develop hypocalcaemia and the slope may indicate whether the hypocalcaemia will be temporary or permanent. Patients with toxic goitres and those having a one-stage total thyroidectomy are most at risk of developing hypocalcaemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
71
2
8

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(86 citation statements)
references
References 24 publications
5
71
2
8
Order By: Relevance
“…First of all, the definition of hypocalcemic symptom is subjective and arbitrary, and many previous studies have used their own definitions (13,(24)(25)(26)(27)(28)(29). The result of this study may be biased by the threshold for pain or tingling sensation of the patients.…”
Section: Discussionmentioning
confidence: 99%
“…First of all, the definition of hypocalcemic symptom is subjective and arbitrary, and many previous studies have used their own definitions (13,(24)(25)(26)(27)(28)(29). The result of this study may be biased by the threshold for pain or tingling sensation of the patients.…”
Section: Discussionmentioning
confidence: 99%
“…RLS zedelenmesi özellikle bilateral olduğunda glottik yetmezliğe yol açtığından ciddi sorun yaratır. Tek taraflı paralizili olgular %30-50 oranında asemptomatik seyredebilmektedir (8,9). Kalıcı RLS hasarı total tiroidektomide yaklaşık %1-1,5'tir.…”
Section: Discussionunclassified
“…Pflederer et al reported a prospective cohort involving 162 patients who underwent total or completion thyroidectomy (33). Association test between number of PGs identified and the development of hypocalcemia produced a significant result in post-operative 6 months (Chi =11.4, P=0.022).…”
Section: Permanent Hypocalcemiamentioning
confidence: 99%
“…When no PGs were seen, 70% had normo-calcemia and 30% has temporary hypocalcemia. For those with all PGs identified, 90% developed temporary hypocalcemia and 10% with permanent hypocalcemia, which required exogenous Ca and vitamin D beyond 6 months after operation (33). Similarly, a recently published prospective study by Lang et al with 569 patients who underwent total thyroidectomy for benign disease reported that permanent hypocalcemia, which was defined as requiring exogenous Ca or vitamin D one year after operation, was significantly higher in patient with 4 PGs identified than in patients with 0-1 PGs identified (11.2% vs. 1.5%, P<0.001).…”
Section: Permanent Hypocalcemiamentioning
confidence: 99%